2014
DOI: 10.1073/pnas.1321072111
|View full text |Cite
|
Sign up to set email alerts
|

Resting GABA and glutamate concentrations do not predict visual gamma frequency or amplitude

Abstract: Gamma band oscillations arise in neuronal networks of interconnected GABAergic interneurons and excitatory pyramidal cells. A previous study found a correlation between visual gamma peak frequency, as measured with magnetoencephalography, and resting GABA levels, as measured with magnetic resonance spectroscopy (MRS), in 12 healthy volunteers. If true, this would allow studies in clinical populations testing modulation of this relationship, but this finding has not been replicated. We addressed this important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 38 publications
3
99
2
Order By: Relevance
“…Yet, two recent studies did not find significant correlations between GABA and BOLD in five brain regions [59] or GABA and magnetoencephalography (MEG) peak gamma levels [60] while two other studies in the insula found a positive correlation between BOLD signal and GABA+ levels [61] and BOLD signal and GABA/NAA levels [62]. In this study, our data revealed a relationship between higher GABA and greater visual plasticity, which may seem counterintuitive.…”
Section: Discussioncontrasting
confidence: 78%
“…Yet, two recent studies did not find significant correlations between GABA and BOLD in five brain regions [59] or GABA and magnetoencephalography (MEG) peak gamma levels [60] while two other studies in the insula found a positive correlation between BOLD signal and GABA+ levels [61] and BOLD signal and GABA/NAA levels [62]. In this study, our data revealed a relationship between higher GABA and greater visual plasticity, which may seem counterintuitive.…”
Section: Discussioncontrasting
confidence: 78%
“…Cousijn et al, 2014; Muthukumaraswamy et al, 2009]. Invigorating this debate, a very recent flumazenil‐positron emission tomography (PET) study demonstrated a positive correlation between the frequency of visually induced gamma oscillations and the density of GABA A receptors in early visual areas [Kujala et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…This position is also supported by pharmalogical manipulations of GABA, as administration of propofol (a GABA agonist) leads to an increase in induced gamma band power (Saxena, Muthukumaraswamy, & Diukova, 2013). However, other studies have not found any association between GABA levels (in occipital cortex) and induced gamma band power (Cousijn et al, 2014;Muthukumaraswamy, Edden, Jones, Swettenham, & Singh, 2009). Therefore currently, it seems that little can be learnt about E/I balance by measuring gamma power in ASD.…”
Section: High Frequency Neural Oscillations (Gamma-band Activity)mentioning
confidence: 92%
“…Peak gamma frequency has been shown to be stable over time, and also to be highly heritable (van Pelt, Boomsma, & Fries, 2012), therefore peak gamma frequency may represent a more useful way to investigate E/I balance in human participants. Some studies have shown that visuallyinduced peak gamma frequency is correlated with resting GABA levels in occipital cortex Gaetz, Edgar, Wang, & Roberts, 2011;Muthukumaraswamy et al, 2009) although others have failed to replicate this relationship (Cousijn et al, 2014;Saxena et al, 2013). The technical difficulty in measuring GABA concentration in vivo with MRS and the different scan parameters used in these studies may contribute to the lack of convergence in results, Nevertheless, peak gamma frequency elicited by visual stimuli has been found to be higher in ASD (Dickinson et al, 2016), and correlated with autistic traits in the neurotypical population (Dickinson, Bruyns-Haylett, Jones, & Milne, 2015).…”
Section: High Frequency Neural Oscillations (Gamma-band Activity)mentioning
confidence: 99%